Targeted gonadotrophin stimulation using the PIVET algorithm markedly reduces the risk of OHSS - Yovich, John; Stanger, J.; Hinchliffe, P. (2012)
PIVET Medical Centre has developed an empirical algorithm for the dose of FSH administration based upon day-2 FSH, antral follicle count, anti-Müllerian hormone, body mass index, age and smoking parameters in an attempt to reduce the incidence of ovarian hyperstimulation syndrome particularly in at-risk women with elevated antral follicle count and anti-Müllerian hormone. The algorithm utilized the incremental dosage capabilities of the recombinant FSH pens to fine-tune the daily concentration of FSH. Application of the algorithm aimed to minimize any form of excessive follicle recruitment that necessitated increased clinical awareness. The measure used to assess the impact of the algorithm was the number of women who, after oocyte retrieval, were considered to be potentially at risk of any degree of OHSS and were allocated to increased monitoring. Compared with the previous 20-month period, introduction of the algorithm significantly reduced both the incidence of referral for increased monitoring, treatment for OHSS and the incidence of freeze-all cycles (all P < 0.05). This was particularly focused on those considered to be at risk without reducing the fresh cycle pregnancy rate. © 2011 Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.